Drying kinetics of cotton based yarn bobbins in a pressurized hot-air convective dryer. (April 2017) - Akal, Dinçer; Kahveci, Kamil; Akyol, Ugur; Cihan, Ahmet
In this study, the drying kinetics of cotton bobbin drying process in a pressurized hot-air convective bobbin dryer was investigated, and a drying model was introduced for the simulation of drying. Tests were conducted for drying temperatures of 70℃, 80℃, and 90℃; effective drying air pressures of 1, 2, and 3 bars; three volumetric flow rates of 42.5, 55, and 67.5 m 3 /h; and for three different bobbin diameters of 10, 14, and 18 cm. Optimum drying conditions were specified in terms of drying time and energy consumption. Results indicate that the total drying time depends significantly on the drying temperature, pressure, and volumetric flow rate. Results show that the minimum energy consumption is obtained for low values of drying air temperatures and pressures, and for moderate and high values of drying air volumetric flow rates. It was also found that the Page model is suitable for simulating the drying behavior of cotton yarn bobbins. Finally, results show that effective diffusion coefficient values are between 1.132 × 10 −7 m 2 /s and 3.453×10 −7 m 2 /s depending on the values of drying parameters.